Use of a genomic classifier in patients with interstitial lung disease: a systematic review and meta-analysis - Kheir, Fayez; Becerra, Juan Pablo Uribe; Bissell, Brittany; Ghazipura, Marya; Herman, Derrick; Hon, Stephanie M.; Hossain, Tanzib; Khor, Yet H.; Knight, Shandra L.; Kreuter, Michael; Macrea, Madalina; Mammen, Manoj J.; et al. (Annals of the American Thoracic Society, 2022)
Background: Usual interstitial pneumonia (UIP) is the histopathologic hallmark of idiopathic pulmonary fibrosis (IPF), the prototypical interstitial lung disease (ILD). Diagnosis of IPF requires th...
Accepted: June 02, 2021
Gesehen am 11.08.2022